Етика і казуїстика в судово-медичній експертизі - Нетудихатка, Олег Юрійович; Нетудыхатка, Олег Юрьевич; Netudyhatka, Oleg (My University, 2012)
Each case of examination isn’t similar on any another, represents «terra incognita» and acts as casuistic option. Ability in ordinary supervision to see and show it to feature is a necessary quality of the doctor which became an expert. As preconditions to ability to find atypical in usual, at first sight the phenomenon serve not only special expert knowledge, not only fundamental medical preparation, but also a broad outlook. Thus, in the field of forensic medicine, knowledge of art of communication and psychological features of the opponent are necessary for each professional and the expert. Natural abilities and formation of ability of creation of the relations with people are thus equally important, to find an approach to them, to gain, as it creates a basis of vital and professional success.
Нетудихатка О. Ю. Етика і казуїстика в судово-медичній експертизі / О. Ю. Нетудихатка // Наукові праці Національного університету «Одеська юридична академія» : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю. П. Аленін [та ін.] ; відпов. за вип. В. М. Дрьомін ; МОН України, НУ ОЮА. – Одеса : Юрид. л-ра, 2012. – Т. 11. – С. 421-428.
Keywords: судова медицина; казуїстика; експертиза; етика; співвідносини; судебная медицина; казуистика; экспертиза; этика; взаимоотношения; forensic medicine; casuistry; examination; ethics; relationship